Origin of Parisian Laws and Regulations in India: “Fons et origo of Zoroastrianism” (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present article is elucidation of Parsi’s and their personal laws to make it a less confused and morecomprehensible study matter. The title “Fons et origo of Zoroastrianism” means the source or the origin ofZoroastrianism. Those who believed that there’s only one Supreme God namely “Ahura Mazda” are knownas Zoroastrians. The researcher has discussed the status of Parsis from its inception till date. This piece ofwork starts with a detailed study of their origin, simplifying their upbringing and tracing their movements andfurther stressing on the enactment & application of their laws in India. This piece of literature, emphasizingon the origin of the Zoroastrians further focuses on the legal provisions relating to Parsi marriages, divorceand maintenance as well. In Toto it’s a compilation of the most needed information and majorly requiredprovisos relating to Parsis.